Vloga medicinske sestre v očesni diagnostiki - Blažič, Marta (Obzornik zdravstvene nege, 2000)
The article describes the work of nurse in eye diagnostics as a specific part of ophthalmology. Nurse has an important role in preparation of a patient for the procedure, as well as during and after it. Explanation of the purpose and methods of the recording and communication as a composite part of modern nursing are presented. Additional knowledge from computers and digital photography is absolutely necessary for the use of modern diagnostic and therapeutic resources. Patient data in electronic format required by the physician for the procedure should be updated and accurate.
Keywords: Diagnosis; diagnostika; Education, nursing; Eye diseases; Fluorescein angiography; Injections, intravenous; medicinske sestre; Nursing diagnosis; Nursing process; Nursing records; očesne bolezni; Patient care team